(untitled) (Proceedings of Southern Federal University. Philology, 2023)
DOI 10.18522/1995-0640-2023-4-80-87 The proposed article describes the functional and pragmatic opportunities of the structural elements of the Russian social media with an emphasis on their stylistic characteristics. The range of issues selected for highlighting consists of an analysis of the basic lexical and syntactic agents involved not only in the heading complex, but also in the general content. In the process of studying the designated question, it is proved that the main purpose of paths and figures of speech in the media is to convey the hidden self-proposition of a journalist, influence the reader and cause an emotional response to him. Headings with expression techniques reflect the author’s position better, thus affects the world view of the reader, his attitude to the describing events. It make the recipient rethink some shades of information and covert meanings. Therefore, they attract the recipient into internal discussion rather faster, they force him to analyze the situation and subsequently set the direction of actions. Key words: рress, headline, headline complex, pragmatics, suggestion, trope, expressive syntax